Semilobar Holoprosencephaly Caused by a Novel and De Novo ZIC2 Pathogenic Variant - Nonkulovski, Danilo; Sofijanova, Aspazija; Spasovska, T; Milanovski, Gorjan; Muaremoska-Kanzoska, Ljelja; Arsov, Todor (Walter de Gruyter GmbH, 2023)
Holoprosencephaly (HPE) is the most common embryonic forebrain developmental anomaly. It involves incomplete or absent division of the prosencephalon into two distinct cerebral hemispheres during the early stages of organogenesis. HPE is etiologically heterogeneous, and its clinical presentation is very variable. We report a case of a 7 month old female infant, diagnosed with non-syndromic semilobar holoprosencephaly, caused by a novel, de novo pathogenic variant in ZIC2 - one of the most commonly mutated genes in non-syndromic HPE coding for the ZIC2 transcription factor. The patient presented with microcephaly, mild facial dysmorphic features, central hypotonia and spasticity on all four extremities. Ultrasound imaging demonstrated the absence of septum pellucidum, semilobar fusion of the hemispheres and mega cisterna magna and brain MRI with confirmed the diagnosis of HPE. Early diagnosis and management are important for the prevention and treatment of complications associated with this condition.